PERANAN BADAN ARSIP DAN PERPUSTAKAAN PROVINSI RIAU DALAM PENELITIAN SEJARAH - Dani, Gusti Rahman; Melay, Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Riau Province has an Archive Board which is part of the Library Board, archives and documentation. Library, Archives and Documentation Board (BPAD) Riau Province based on Perda No.8 of 2008, is the development of the organization of the Library and Archives of Riau Province. Riau Archive and Library Board is an institution or agency under the auspices of the Riau Provincial Government which has the duty and authority in managing Dynamic and static archives either in the form of state documents or regional government as well as documents that have historical value that have good value either in Forms of written documents and digital forms that will be stored and maintained through archiving and library agencies. The purpose of this research is to know the history of the establishment of the Archives And Library of Riau Province. To know the task and authority of Riau Archive and Library Board. To know the role of Archive Board which is part of the Library Board Riau Province. The methods used in this research are historical and qualitative approaches. Data obtained from interviews and library sources will be developed by using their own language. The research location is in Pekanbaru City Riau Province. The time of this research started since the issuance of SK Dean of FKIP-Universitas Riau to do research until the time limit until thesis seminar. Data collection techniques used are obsevation techniques, interview techniques, documentation techniques and literature study techniques. From the results of research has been found that the Archives and Libraries of Riau Province is very active role in providing information about the sources in conducting research and writing history for all people and students.Keywords: Archive Board, Library, Riau Province